Electronic structure methods for complex materials the orthogonalized linear combination of atomic orbitals - Ching, Wai-Yim.; Rulis, Paul Michael, 1976- (Oxford : Oxford University Press, 2012)
This title details the application of the OLCAO method for calculating the properties of solids from fundamental principles to a wide array of material systems. The method specialises in large and complex models and is able to compute a variety of useful properties including electronic, optical, and spectroscopic properties.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Atomic orbitals; Electronic structure; Density functionals